Can solar neutrinos be a serious background in direct dark matter searches? - Vergados, Ioannis; Ejiri, Hiroko (My University, 2008)
The coherent contribution of all neutrons in neutrino nucleus scattering due to the neutral current is examined considering the boron solar neutrinos. These neutrinos could potentially become a source of background in the future dark matter searches aiming at nucleon cross sections in the region well below the 10(-10) pb, i.e. a few events per ton per year.
Keywords: Form-factors; Event rates; Wimp search; Modulation; Constraints; Candidates